Ferromagnetic excess moments and apparent exchange bias in FeF(2) single crystals - Joshi, D. C. (Sci Rep, 2019)
The anisotropic antiferromagnet FeF(2) has been extensively used as an antiferromagnetic layer to induce exchange bias effects in ferromagnetic/antiferromagnetic bilayers and heterostructures. In this work, an apparent exchange bias occurring in the low temperature hysteresis loops of FeF(2) single crystals is investigated. A detailed investigation of the hysteresis and remnant magnetization indicates that the observation of an apparent exchange bias in FeF(2) stems from an intrinsic excess moment associated with a distortion of the antiferromagnetic structure of piezomagnetic origin.